Waste Identification and Root Cause Analysis in the Roasted Onion Seasoning Production Process at PT. AFI - Adila Amanda; Dino Rimantho (Jurnal Konversi Energi dan Manufaktur, 2026)
PT. AFI is a manufacturing enterprise that manufactures a variety of seasonings, including roasted onions. The organization must consistently manufacture high-quality items by optimizing production outcomes and enhancing productivity. Nevertheless, waste impedes the company's efficiency in executing its production processes. Waste potential can arise in any company activities, as evidenced by PT. AFI's experience. This study seeks to detect and analyze waste generated during the production process of roasted onion flavoring. The waste manifests as poor products, transportation inefficiencies, unnecessary movement, and idle time. This article employs seven tools and a fishbone diagram as its methodology. The identification results indicate that the waste from defective items in production totals 7.25 kg. Furthermore, a transportation activity method necessitates a total duration of 30.52 minutes. Furthermore, excessive mobility during the production process is documented at 19.14 minutes. The identification results indicate multiple elements contributing to waste, including personnel, machinery, processes, materials, and environmental conditions.